The challenge : a novel - Steel, Danielle (New York : Random House Inc, 2022)
"A small community is tested when their children go missing while exploring a dangerous local peak, forcing them to band together during the crisis."--provided by publisher.
Keywords: Missing children -- Fiction; Families -- Fiction; Family secrets -- Fiction; Best friends -- Fiction; Wilderness survival -- Fiction; Search and rescue operations -- Fiction; Fishtail (Mont.) -- Fiction; Montana -- Fiction; Beartooth Mountains (Mont. and Wyo.) -- Fiction; Large type books; Domestic fiction